The battle of Dorking; reminiscences of a volunteer - Chesney, George Tomkyns, 1830-1895 (W. Blackwood and Sons, 1871)
An imaginary story of an invasion and defeat of Great Britain by Germany ca. 1875, inspired by the defeat of France in the Franco-Prussian War.